Exploration of bioflavonoids targeting dengue virus NS5 RNA-dependent RNA polymerase: In silico molecular docking approach - Dhanasekaran Sivaraman, Pushparaj Selvadoss Pradeep (Journal of Applied Pharmaceutical Science, 2020)
Dengue viral infection becomes highly epidemic and rashes the economic stability of most of the developing countries due to its wide prevalence with limited therapeutic ailments. Alarming demographic data urge the need for the development of new antiviral agents which are safe and efficacious. This study aimed to evaluate the antiviral potential of bioflavonoids (apigenin, hesperidin, kaempferol, myricetin, and naringenin) against dengue virus nonstructural (NS)5 RNA-dependent RNA polymerase (RdRp) by AutoDock and tox prediction tools. The results of molecular docking analysis strongly suggested that the lead phytocomponents such as apigenin, hesperidin, and kaempferol reveal potential RdRp inhibition as ascertained by its interaction with core active amino acid residues (710 SER, 729 ARG, and 737 ARG) on the target. Apigenin exhibited the best binding affinity of −8.28 kcal/mol with RdRp, followed by kaempferol (−7.00 kcal/mol), myricetin (−4.37 kcal/mol), naringenin (−4.35 kcal/mol), and hesperidin(−3.20 kcal/ mol). The present research finding clearly advocates that plant-derived bioflavonoids possess excellent antiviral property against the selected target.
Keywords: Dengue viral infection, bioflavonoids, RNA-dependent RNA polymerase inhibitors, apigenin, hesperidin, kaempferol.